VERIFIKASI DAN VALIDASI HASIL VISITASI DALAM MENDUKUNG KREDIBILITAS AKREDITASI LEMBAGA PENDIDIKAN - Istiqomah; Hilmi Mizani; Husnul Yaqin (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze the role of verification and validation of visitation results in supporting the credibility of educational institution accreditation as part of the educational quality assurance system. The study employed a qualitative approach using a library research method by reviewing scientific literature, journal articles, and official documents related to visitation, verification, validation, and educational accreditation. Data were analyzed descriptively through data reduction, classification, and synthesis techniques. The findings reveal that verification functions to ensure the conformity of visitation data with supporting evidence and documents, while validation aims to ensure the accuracy, consistency, and feasibility of the data as the basis for accreditation decisions. The verification and validation process is conducted systematically through stages of data collection, examination, clarification, validation, and final determination. In addition, the application of objectivity, transparency, accountability, consistency, and professionalism principles plays an essential role in maintaining the quality and credibility of accreditation results. Therefore, verification and validation have a strategic role in improving the credibility of accreditation outcomes and supporting accurate and reliable data-based educational decision-making.